NF-κB in Anti-Inflammatory Activity of Probiotics: An Update - Virginia Rodriguez, Ana; Griet, Milagros (Current Immunology Reviews (Discontinued), 2016)
The NF-κB (nuclear factor κappa B) belongs to a family of transcription factors that regulate a number of key cellular pathways and control many physiological processes, including the immune and inflammatory responses. The beneficial effect of probiotics is presently recognized in both the intestinal and extra-intestinal development. The growing literature on the subject suggests an important role of specific probiotic strains, mixtures of strains, and secreted products, all of which have a role in either the preventive or therapeutic treatment of certain human disorders. During the last two decades, a number of studies have shown that probiotic strains and their extracellular products can join the immune system and activate receptors in different key pro-inflammatory pathways such as the NF-κB route, either by increasing or suppressing the signaling pathways. This brief review does not include an exhaustive bibliography of the subject, but focuses instead on an update to the latest research of the past three years on the role of the NF-κB signaling pathway in the anti-inflammatory effect of probiotics.
Keywords: probiotic-host interaction